Socio-Emotional and Cognitive Resilience in Children with Reading Disabilities - Haft, Stephanie L. (Curr Opin Behav Sci, 2016)
In recent times, research on resilience in children facing adversities has proliferated. In this review, the authors characterize resilience in children with reading disorders (RD). To organize our discussion and categorize the specific outcomes such children demonstrate, we adopt the terms cognitive resilience and socio-emotional resilience. By paralleling other resilience research, we seek to uncover protective factors in the hopes that they can be targeted in education and interventions to improve cognitive functioning, socio-emotional wellbeing, and academic success of children with RD. We conclude by considering current limitations and addressing the need for future resilience research in this specific population of children.